Quantitative correlation between mammographic breast density according to BI-RADS and ultrasound echo intensity / Faikah Awang @ Ismail - Awang @ Ismail, Faikah (2014)
The purpose of this research was to find out the correlation between mammography breast density according to BI-RADS classification and ultrasound echo intensity. The research was carried out at the Women Cancer Detection and Breast Clinic, National Cancer Society, Kuala Lumpur through two sessions of data collection. Three hundred Malaysian women aged between 40 and 60 years volunteered to become subjects. All subjects were free from breast pathology and breast surgery. The modalities used in this research were mammography and ultrasound. Each subject was given a brief explanation of the research to be carried out and a letter of consent had to be signed before she could participate. Subjects were identified via their mammography number. Subject’s background data was obtained via patient’s database except their BMI. The ultrasound examination was done after the completion of mammography examination to ensure subject was free from interval breast pathology. All images were stored in data storage for analysis. BI-RADS classification was carried out by four experienced radiologists to prevent bias during BI-RADS reporting. BI-RADS breast density was classified into four classes: BI-RADS I, BI-RADS II, BI-RADS III and BI-RADS IV. Ultrasound images were processed using QLab software for echo intensity reading. Data were processed using Microsoft Excel version 2007 and SPSS version 15.0. Weak but significant Spearman’s Rho correlation (rs = 0.305, p = 0.001) was found as the primary finding on correlation between mammography breast density according to BI-RADS and ultrasound echo intensity.